"Do you understand what you are reading?" --rhetoric, ethics and aesthetics in the undergraduate classroom. (March 2016) - Bowen, Deborah C
Universities have a perhaps unique opportunity to provide training in the art of deep reading through attention to the interrelation of rhetoric, ethics, and aesthetics. While rhetorically sensitive reading will help students to become more sophisticated readers of voice and worldview, and ethically charitable reading will help them to become more sensitive to their neighbors both inside and outside of books, aesthetically delighted reading will give them the kind of sustained enjoyment that enriches and inspires the imagination. These modes of deep reading will defend them against the impoverished imagery, manipulative strategies and flashy narrative techniques of much commercial culture.